|
|
Line 46: |
Line 46: |
| | | |
| As a check: | | As a check: |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | \left( \frac{q}{k} \right)^2 |
| + | & = \left( \frac{x}{ \sqrt{x^2 + d^2 + z^2 d^2 }} \right)^2 + \left( \frac{d - \sqrt{x^2 + d^2 + z^2 d^2 } }{\sqrt{x^2 + d^2 + z^2 d^2 }} \right)^2 + \left( \frac{z d }{\sqrt{x^2 + d^2 + z^2 d^2 }} \right)^2 \\ |
| + | & = \frac{x^2 + \left( d - \sqrt{x^2 + d^2 + z^2 d^2 }\right)^2 + z^2d^2 }{x^2 + d^2 + z^2d^2} \\ |
| + | & = \frac{x^2 + \left( d^2 - 2d \sqrt{x^2 + d^2 + z^2 d^2} + x^2 + d^2 + z^2 d^2 \right) + z^2d^2 }{x^2 + d^2 + z^2d^2} \\ |
| + | & = \frac{2 x^2 + 2 d^2 + 2 z^2d^2 - 2d \sqrt{x^2 + d^2 + z^2 d^2} }{x^2 + d^2 + z^2d^2} \\ |
| + | & = 2 \frac{( x^2 + d^2 + z^2d^2 ) - d \sqrt{x^2 + d^2 + z^2 d^2} }{x^2 + d^2 + z^2d^2} \\ |
| + | & = 2 \left( 1 - \frac{d}{\sqrt{x^2 + d^2 + z^2d^2}} \right) |
| + | \end{alignat} |
| + | </math> |
| | | |
| ====Working results 2 (contains errors)==== | | ====Working results 2 (contains errors)==== |
Revision as of 12:31, 13 January 2016
Working results 1
![{\displaystyle {\begin{alignedat}{2}\mathbf {q} &={\frac {2\pi }{\lambda }}{\begin{bmatrix}\sin \theta _{f}\cos \alpha _{f}\\\cos \theta _{f}\cos \alpha _{f}-1\\\sin \alpha _{f}\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}\sin \left(\arctan \left[{\frac {x}{d}}\right]\right)\cos \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)\\\cos \left(\arctan \left[{\frac {x}{d}}\right]\right)\cos \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)-1\\\sin \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}{\frac {x/d}{\sqrt {1+\left(x/d\right)^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\\{\frac {1}{\sqrt {1+\left(x/d\right)^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}-1\\{\frac {z\cos \theta _{f}}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}{\frac {xd}{\sqrt {d^{2}+x^{2}}}}{\frac {1}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\\{\frac {d}{\sqrt {d^{2}+x^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}-1\\{\frac {z\cos \theta _{f}}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\end{bmatrix}}\\\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/6ea671cecdf06e0446180db0c1e73d2bb4fd81a5)
Note that
, and
so:

And:

As a check:

Working results 2 (contains errors)
As a check of these results, consider:

Where we used:
![{\displaystyle {\begin{alignedat}{2}\sin(\arctan[u])&={\frac {u}{\sqrt {1+u^{2}}}}\\\sin \theta _{f}&=\sin(\arctan[x/d])\\&={\frac {x/d}{\sqrt {1+(x/d)^{2}}}}\\&={\frac {x}{\sqrt {d^{2}+x^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/fc9628f0d308053600f4e02d8f80c69fc9f356d0)
And, we further note that:
![{\displaystyle {\begin{alignedat}{2}\cos(\arctan[u])&={\frac {1}{\sqrt {1+u^{2}}}}\\\cos \theta _{f}&={\frac {1}{\sqrt {1+(x/d)^{2}}}}\\&={\frac {d^{2}}{\sqrt {d^{2}+x^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/584da470743b7feac2b55988526dabce5b4313c4)
Continuing:
